Five Year Retrospective Study of Profile of Burn Deaths from Pune Region (Medico Legal Update, 2020)
A burn is an injury which is caused by application of heat or chemical substances to the external or internalsurfaces of the body, which causes destruction of the tissues. The magnitude of deaths due to burns is solarge in our country that India is the only country in the world where fire is classified among the fifteenleading causes of death. The purpose of this study is to analyze profile of burn deaths in the Pune region ofMaharashtra. In the present study among the 1710 burn deaths, females (70%) are more commonly affectedthan males (30%). Young adults (21–40 yrs) are commonly involved in fatal burns as this is most activegroup of population. In present study majority cases happened in summer season and were accidental innature while suicidal deaths were present in significant number. Flame burns comprised of 80% of the casesfollowed by scald 13%. In 78% of cases more than 50 % of total body surface area was involved whilecomplications like Septicemia (66%) was commonest cause of death.